Impact of polycystic ovary syndrome on the development and course of type 2 diabetes mellitus: a comparative cross-sectional study (Uzbekistan Open Conference, 2026)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age and is considered a systemic metabolic disease. In addition to reproductive dysfunction, PCOS is associated with significant metabolic abnormalities, particularly insulin resistance, obesity, and dyslipidemia, which substantially increase the risk of type 2 diabetes mellitus (T2DM). This study aimed to evaluate the influence of PCOS on the clinical and metabolic characteristics of T2DM in women. The study included 60 women with T2DM aged 38–40 years. Patients were divided into two groups: the main group consisted of 30 women with PCOS and T2DM, while the control group included 30 women with T2DM without PCOS. Body mass index (BMI), glycated hemoglobin (HbA1c), insulin resistance index (HOMA-IR), lipid profile parameters, and the presence of arterial hypertension were assessed. Statistical analysis was performed using Student’s t-test and the χ² test, with p<0.05 considered statistically significant. Women with PCOS demonstrated significantly higher BMI values (33.1 ± 4.2 kg/m² vs 29.4 ± 3.6 kg/m²; p<0.001), higher HOMA-IR indices (6.5 ± 1.6 vs 4.2 ± 1.3; p<0.001), and elevated HbA1c levels (9.6 ± 1.3% vs 8.1 ± 1.0%; p<0.001) compared with the control group. Lipid metabolism disorders were identified in 80.0% of patients in the main group and 55.0% in the control group (p=0.033). The findings suggest that PCOS in women with T2DM is associated with more pronounced metabolic disturbances, poorer glycemic control, and increased cardiometabolic risk. These results highlight the importance of early detection, metabolic monitoring, and individualized therapeutic strategies in this patient population.